Evaluation of Serum Fetuin-A as A Possible Marker for Polycystic Ovarian Syndrome Among Iraqi Women; Case-control Study - Ola Jamal Yasien; Fadia J. Al Izzi (Academia Open, 2023)
Elevated levels of Fetuin-A, a protease inhibitor belonging to the cystatin family, have raised questions about its role in the pathogenesis of Polycystic Ovarian Syndrome (PCOS), the most prevalent endocrinopathy in reproductive-aged females. This case-control study, conducted in Iraq, aimed to assess changes in Fetuin-A levels among Iraqi women with PCOS. A convenient sample of 90 women, comprising 45 PCOS cases and 45 healthy controls, was enrolled. Fetuin-A levels were measured and found to be significantly higher in the PCOS group compared to controls. Additionally, significant positive correlations were observed between Fetuin-A levels and fasting plasma glucose, fasting serum insulin, insulin resistance, luteinizing hormone, and serum testosterone. Using a receiver operating characteristic curve, a cutoff point of 502.00 ng/mL was determined for predicting positive Fetuin-A levels, with a sensitivity and specificity of 84.4% and 73.3%, respectively. This study suggests that Fetuin-A could serve as a valuable marker for both screening and evaluating PCOS and its potential late consequences, including metabolic syndrome. Highlights: Elevated Fetuin-A Levels: This study reveals significantly higher Fetuin-A levels in PCOS, shedding light on its potential role in the pathogenesis of the syndrome. Correlations with Metabolic Factors: Positive correlations between Fetuin-A and key metabolic markers like fasting glucose, insulin resistance, and luteinizing hormone highlight its relevance in the context of PCOS and metabolic health. Screening Potential: The identified cutoff point for predicting positive Fetuin-A levels offers a promising tool for screening and evaluating PCOS and associated late consequences, particularly metabolic syndrome.